Natureza humana na educação em ciências: uma reflexão filosófica - Rosa, Vinícius Medeiros da (2019)
This research investigates how a group of professors, graduate students in Science Teaching, establishes relationships between human nature, philosophy of education and epistemology of science. From this investigation, reflections on the implications of human nature in science education were made. A set of classes was prepared and implemented in a discipline of the Graduate Program in Science Education: Chemistry of Life and Health. We have taken as theoretical basis the ideas contained in some writings of Jacques Maritain, a French philosopher of the twentieth century known as a neotomist. Our hypothesis is that the relationship between human nature and philosophy of education is a direct one, since the educational system is built upon a concept of human nature that underlies the human being to be educated, and all educational activity. Science, as we know it from the sixteenth century, have had a great influence on the two points mentioned above; thus, a better understanding of how this relationship occurs in Jacques Maritain's thinking can help science education contribute to integral human development. The data obtained by the research instruments were analyzed through the Grounded Theory (STRAUS AND CORBIN, 2008; CHARMAZ, 2009), and the results revealed that the research participants established some relationships between the three above-mentioned themes, predominantly indirectly, but also directly. The students presented evidence that the teachers' philosophy of education should be explicit, and that it is influenced by their concept of human being, also that theirs conceptions of science affect the teaching practice. Moreover, the epistemology of science presented potential to foster discussions on the other two topics.